2023
DOI: 10.2147/idr.s400451
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spine Infection with Eikenella corrodens Presented as Abdominal Pain: A Case Report and Literature Review

Abstract: Background: Eikenella corrodens is a part of the inherent flora on the surface of human mucosa. It usually does not cause disease unless the patient has been bitten, injured or surgically infected. Lumbar spine infection caused by Eikenella corrodens usually presents with conventional symptoms such as low back pain and fever. Herein, we report a case of lumbar intervertebral space infection with Eikenella corrodens presented as abdominal pain. Case Presentation: A 38-year-old man with no medical history of not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In recent years, with the declining cost of sequencing, mNGS has been implemented in clinical practice, offering substantial benefits to patients with suspected spinal infections. 7 Herein, a retrospective study was conducted to evaluate the accuracy and validity of mNGS in diagnosing spinal infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the declining cost of sequencing, mNGS has been implemented in clinical practice, offering substantial benefits to patients with suspected spinal infections. 7 Herein, a retrospective study was conducted to evaluate the accuracy and validity of mNGS in diagnosing spinal infections.…”
Section: Introductionmentioning
confidence: 99%
“…5 Given that the mNGS technique enables rapid and impartial culture-independent diagnosis, it has been adopted in clinical laboratories for pneumonia, sepsis, and spinal infection. [6][7][8] In current clinical practice, numerous case reports and retrospective studies have demonstrated the superior diagnostic efficiency of mNGS compared to traditional culture methods. [9][10][11] Moreover, the use of antibiotics significantly undermines the success of traditional cultures, whereas the mNGS technique is minimally affected.…”
Section: Introductionmentioning
confidence: 99%